Accuracy of Flash Glucose Monitoring During Postprandial Rest and Different Walking Conditions in Overweight or Obese Young Adults - Zhang, Xiaoyuan; Sun, Fenghua; Wongpipit, Waris; Huang, Wendy Y. J.; Wong, Stephen H. S. (Frontiers in Physiology, 2021)
Aims: To investigate the accuracy of Freestyle LibreTM flash glucose monitoring (FGM) relevant to plasma glucose (PG) measurements during postprandial rest and different walking conditions in overweight/obese young adults. Methods: Data of 40 overweight/obese participants from two randomized crossover studies were pooled into four trials: 1) sitting (SIT, n = 40); 2) walking continuously for 30 min initiated 20 min before individual postprandial glucose peak (PPGP) (20iP+CONT, n = 40); 3) walking continuously for 30 min initiated at PPGP (iP+CONT, n = 20); and 4) accumulated walking for 30 min initiated 20 min before PPGP (20iP+ACCU, n = 20). Paired FGM and PG were measured 4 h following breakfast. Results: The overall mean absolute relative difference between PG and FGM readings was 16.4 ± 8.6% for SIT, 16.2 ± 4.7% for 20iP+CONT, 16.7 ± 12.2% for iP+CONT, and 19.1 ± 6.8% for 20iP+ACCU. The Bland–Altman analysis showed a bias of −1.03 mmol·L−1 in SIT, −0.89 mmol·L−1 in 20iP+CONT, −0.82 mmol·L−1 in iP+CONT, and −1.23 mmol·L−1 in 20iP+ACCU. The Clarke error grid analysis showed that 99.6%–100% of the values in all trials fell within zones A and B. Conclusions: Although FGM readings underestimated PG, the FGM accuracy was overall clinically acceptable during postprandial rest and walking in overweight/obese young adults.